GUIDANCE OF ISLAMIC RELIGIOUS EDUCATION TEACHERS IN INSTILLING FAIR CHARACTER IN STUDENTS DURING THE PANDEMIC - Moh. Sholihuddin (Institut Keislaman Abdullah Faqih (INKAFA) Gresik, 2022)
Abstract: A teacher, in addition to serving in teaching he also has a task in giving bimbingan to students. Of course, it does not have to be like a Counselor who in his job is to help clients solve problems in their clients' personal lives, but the guidance of the teacher in ques-tion is to direct students to be better. The guidance certainly also pays attention to positive and religious values. then it is natural that teachers must be a good tauladan, so that the upbringing participants feelin-spired and motivated. In this article discusses how the guidance of Islamic Religious Education teachers in instilling a fair character in the learners who are interviewed from the teacher. This article is the result of research on several elementary school teachers in Lasem Rembang. Results from data collected through interviews and obesrvasi. The results showed that the guidance of Islamic religious education teachers in instilling a fair character in students is through teacher transparency in providing assessment of student learning outcomes and learning in the form of methods of telling the stories of prophets in the Qur'an that tells about justice.Keywords: Character; learning outcomes;